IMPACT OF CLIMATE CHANGE ON AGRICULTURE: CONTRIBUTIONS AND LIMITATIONS OF RICARDIAN STUDIES. - (:unkn) unknown (My University, 2018)
In this thesis, we show that although the Ricardian model widely contributes to the analysis of climate change impact on agriculture, it is not always adequate for developing countries, especially in Africa. We therefore explain in the first chapter, through an analysis of the literature, the Ricardian model birth circumstances, the studies using this model, the criticisms and the proposed new approaches. It comes out that the debate continues on "the best approach" to use in assessing the impact of climate change on agriculture. The second chapter, taking the case of Côte d'Ivoire, shows us Ivoirian farmers revenues of the Center and North decrease against an unfavorable future climate. This analysis is a significant contribution of the Ricardian model because this country has never benefited from this type of study and the climate zone approach has made it possible to be more precise in impact measurements. Finally, the last chapter demonstrates that price bias is one of the limits that negatively affects the Ricardian model used for African countries. Based on Burkina Faso, we thus show that this bias leads to an underestimation of the impact of climate change on agriculture in Africa.
Keywords: African Research